Alphabet Mystery Box Media to Improve Early Reading Literacy in Early Childhood - Lili, Waode; Hayati, Nur; Christianti, Martha (JURNAL PENDIDIKAN USIA DINI, 2025)
The purpose of this study was to determine the effect of using the alphabet mystery box media on early reading skills in early childhood. The literature review was conducted using Google Scholar, Google Search, hyperlinks, and ResearchGate. A total of 13 peer-reviewed publications, dated between 2020 and 2024, were included in the review, which included studies in English and Indonesian. Data analysis used content analysis to examine findings related to the Alphabet Mystery Box media and its effect on early childhood reading skills, contextualized in relevant theories and previous research. The results of the study indicate that early reading skills through the use of alphabet box media for early childhood have a significant impact on early literacy skills. The use of "magic box" learning media can improve children's cognitive and language skills, including recognizing numbers, alphabets, and colors. This article aims to optimize the reading skills of children aged 0-6 years, which is considered a critical developmental period. This study can assess how integrating traditional and digital media affects the engagement and effectiveness of early reading instruction.